The Effects of the Aqueous Extract of the Leaves of the Local Plant Eruca sativa on Lipid Profile and Some Minerals in the Blood of Male White Mice - Weli, Sardar Mohammed; Kareem, Sattar Ibrahim; Shareef, Osama Hamid; Rauf, Hwda Ghafoor; Raouf, Chro Ghafoor; Hama, Abdullah Ahmed (Iraqi Journal of Science, 2021)
Eruca sativa, commonly known as rocket salad, is a popular vegetable to which a wide range of health benefits are attributed. This study aimed to examine the effects of the aqueous extract of E. sativa leaves on lipid profile and some minerals, such as calcium and magnesium, in blood of male albino mice under normal physiological condition. Two experiments were separately conducted, each with eighteen male albino mice divided into 3 equal groups, which included control, treated group (1), and treated group (2) which were orally administrated with 0, 0.2 and 0.4 mg/kg body weight, respectively, of the leaves extract for 28 days. In the first experiment, serum lipid profile, including cholesterol, triglyceride, HDL, LDL and VLDL, were estimated. In the second experiment, serum calcium and magnesium were estimated. The results showed that E. sativa have effects on lipid profile by decreasing cholesterol, triglyceride, and LDL levels, but increasing that of HDL. In addition, E. sativa increased the levels of both calcium and magnesium. This study concludes that E. sativa leaves exerts possibly beneficial effect on lipid profile and calcium and magnesium levels in albino male mice under normal conditions.